Response to Rates of Nitrogen Fertilizer Application of F4 Progenies of Composite Crosses Between Local Rice Variety (Mueang Nga) and High Yielding Variety (Thadokkham7) of Lao PDR - Khemkham Hongphakdy (Agriculture Chiang Mai University, 2019)
Journal of the Faculty of Agriculture, Chiang Mai University. The journal will be publicized every 4 months (January, May and September), which will focus on Agriculture, Agro-Industry, Veterinary and Biology.